Evaluation of the flame propagation within an SI engine using flame imaging and LES. Issue 6 (2nd November 2017) - He, Chao; Kuenne, Guido; Yildar, Esra; van Oijen, Jeroen; di Mare, Francesca; Sadiki, Amsini; Ding, Carl-Philipp; Baum, Elias; Peterson, Brian; Böhm, Benjamin; Janicka, Johannes
Abstract : This work shows experiments and simulations of the fired operation of a spark ignition engine with port-fuelled injection. The test rig considered is an optically accessible single cylinder engine specifically designed at TU Darmstadt for the detailed investigation of in-cylinder processes and model validation. The engine was operated under lean conditions using iso-octane as a substitute for gasoline. Experiments have been conducted to provide a sound database of the combustion process. A planar flame imaging technique has been applied within the swirl- and tumble-planes to provide statistical information on the combustion process to complement a pressure-based comparison between simulation and experiments. This data is then analysed and used to assess the large eddy simulation performed within this work. For the simulation, the engine code KIVA has been extended by the dynamically thickened flame model combined with chemistry reduction by means of pressure dependent tabulation. Sixty cycles have been simulated to perform a statistical evaluation. Based on a detailed comparison with the experimental data, a systematic study has been conducted to obtain insight into the most crucial modelling uncertainties.